Presence and fate of microplastics in the water sources: focus on the role of wastewater and drinking water treatment plants. (April 2021) - Barchiesi, Margherita; Chiavola, Agostina; Di Marcantonio, Camilla; Boni, Maria Rosaria
Graphical abstract: Abstract: Microplastics are nowadays considered as ubiquitous pollutants since have been found widespread in all environmental compartments, particularly in the water sources. In the urban water cycle, the drinking water treatment plants and the wastewater treatment plants are the first and last barriers to microplastics pollution, respectively. The present work aims at presenting the information available on microplastic presence in the urban water cycle, reporting and linking what is known at the different stages. Focus is on the water sources and on the role of the water treatment plants as source and control of microplastics pollution. Aspects evaluated are microplastics abundance, characterization in terms of morphology, size and polymer composition, spatial and temporal variations, factors influencing their distribution and abundance, effects of treatments on their removal. Up to now there is no common framework for microplastics collection, sample pre-treatment, identification, quantification and classification. Data comparison is hindered due to the various analytical protocols implemented; hence the conclusions driven are mostly indicative or of very local significance. The available information is not evenly distributed among the urban water cycle components. For the establishment of proper microplastics pollution control strategies, the relative role of wastewater and drinking water treatment plants needs to be better deepened in terms of both quantity and quality effects. All these aspects are afforded in the present review which is based on the more recent data published by the specialized literature.